A Comparative Study of the Fama-French Three Factor and the Carhart Four Factor Models: Empirical Evidence from Morocco - Tazi, Omar; Aguenaou, Samir; Abrache, Jawad (International Journal of Economics and Financial Issues, 2022)
This paper investigates the validity of the Fama-French Three Factor (FF3F) and the Carhart Four Factor (C4F) models in Morocco. Monthly returns of Casablanca Stock Exchange-listed companies are extracted from Reuters DATASTREAM over a 5 years’ period (2013-2017). Market, size, value and momentum effect-mimicking exogenous variables are formed and regressed against the returns of size and value-sorted portfolios over a total of 8 multivariate linear regressions. While the size and value effects were found to partially hold, the momentum effect was found to be insignificant. Additionally, the C4F Model did not exhibit a better explanatory power compared to the FF3F Model. It appears that both models cannot be fully relied on in order to predict cross-sections of return in the Casablanca Stock Exchange (CSE), as they both only partially hold in the latter. Ultimately, this study brings value to the existing literature by testing two widely explored asset pricing models in an emerging market where equity research-oriented inquiries are relatively scarce or basic. Even if the models do not fully hold in the Moroccan context, this study posits whether the individual anomalistic factors hold in the CSE, which might be useful for future asset pricing models augmenting endeavors.